A gestão portuária e o acúmulo de capacidades tecnológicas no porto do Pecém - Lima, Klayton Cardoso Araújo (2024)
Ports have always been considered a link between water and land, as the water transport system has always been a form of connection between people, initially for subsistence, through major territorial conquests, to the present day serving the large volumes of negotiations between countries. Despite being currently the most used modal for foreign trade, Maritime and Port Logistics needs to constantly review its processes and innovations to meet the exponentially growing demand. Previous studies address the efficiency of port management, innovation, transport capacity in ports, sustainability and the environment, but do not report the integration between port management and the accumulation of technological capacity. Therefore, this study seeks to fill this gap. The general objective of this work was to understand the trajectory of the accumulation of technological capabilities in the Port of Pecém. This study questions how the trajectory of the accumulation of technological capabilities occurred in the Port of Pecém? From this, through an exploratory and descriptive study, with a qualitative nature, capturing information through interviews, bibliographic and documentary research, in addition to field observations, using the case study methodology. Data collection and analysis were divided into two parts. In the first stage, interviews were carried out with four experts from the port area who presented the following main functions in the port area: planning the loading and unloading operation, storage (back port area) and port equipment, with the data presented, adaptation was carried out of the technological capabilities measurement model proposed by Figueiredo (2017) to the port sector, achieving the first specific objective. In the second stage of the research, twenty-one experts from the port area were interviewed, applying the adaptive technology capacity measurement model, using a form that aimed to determine how the accumulation of technological capacity occurred in the functions established in the first phase. of the interviews. After collecting data from the second phase of interviews, the evidence obtained was described and analyzed. This procedure made it possible to map technological capabilities at levels of innovation in the port of Pecém and analyze the evolution of the accumulation of technological capabilities at levels of innovation at the port of Pecém, achieving the second and third specific objectives. The analysis of the results obtained suggests that the port of Pecém has accumulated echnological capacity since its inauguration until 2023. The results reinforce previous studies on how to measure organizations using the technology accumulation method, in addition to this study contributing to adapt the metric for measuring the accumulation of theological capacity for the port area.